Operationalization of a multidimensional sex/gender concept for quantitative environmental health research and implementation in the KORA study: Results of the collaborative research project INGER - Kraus, Ute; Jacke, Katharina; Dandolo, Lisa; Debiak, Malgorzata; Fichter, Sophie; Groth, Katrin; Kolossa-Gehring, Marike; Hartig, Christina; Horstmann, Sophie; Schneider, Alexandra; Palm, Kerstin; Bolte, Gabriele (Frontiers in Public Health, 2023)
Background. In environmental health research, sex and gender are not yet adequately considered. There is a need to improve data collection in population-based environmental health studies by comprehensively surveying sex/gender-related aspects according to gender theoretical concepts. Thus, within the joint project INGER we developed a multidimensional sex/gender concept which we aimed to operationalise and to test the operationalisation for feasibility. Methods. In an iterative process, we created questionnaire modules which quantitatively captured the requirements of the INGER sex/gender concept. We deployed it in the KORA cohort (Cooperative Health Research in the Region of Augsburg, Germany) in 2019 and evaluated response and missing rates. Results. The individual sex/gender self-concept was surveyed via a two-step approach that asked for sex assigned at birth and the current sex/gender identity. Additionally, we used existing tools to query internalised sex/gender roles and externalised sex/gender expressions. Adapted to the KORA population, we asked for discrimination experiences and care and household activities contributing to explain structural sex/gender relations. Further intersectionality-related social categories (e.g. socio-economic position), lifestyle and psychosocial factors were covered through data available in KORA. We could not identify appropriate tools to assess the true biological sex, sexual orientation and ethnic/cultural identity, which have yet to be developed or improved. The response-rate was 71%, the evaluation of 4,373 questionnaires showed a low missing rate. Prevalence of marginalised groups regarding sex/gender identity and definable by experiences of discrimination was very low. Conclusion. We have shown how the multidimensional INGER sex/gender concept can be operationalised according to an European and North American understanding of sex/gender for use in quantitative research. The questionnaire modules proved feasible in an epidemiologic cohort study. Being a balancing act between theoretical concepts and its quantitative implementation our operationalisation paves the way for an adequate consideration of sex/gender in environmental health research.